Effects of caffeine on session ratings of perceived exertion - Killen, L. G.; Green, J. M.; O`Neal, E. K.; McIntosh, J. R.; Hornsby, J.; Coates, T. E. (European Journal of Applied Physiology, 2013)
This study examined effects of caffeine on session ratings of perceived exertion (RPE) following 30 min constant-load cycling. Individuals (n = 15) of varying aerobic fitness completed a VO2 max trial and two 30 min cycling bouts (double-blind, counterbalanced) following ingestion of 6 mL/kg of caffeine or matched placebo. RPE overall, legs and breathing were estimated every 5 min and session RPE was estimated 30 min post-exercise using the OMNI pictorial scale. Session RPE for caffeine and placebo trails were compared using paired t test. Between-trial comparisons of HR, RPE overall, RPE legs and RPE breathing were analyzed using an independent 2 (trial) × 6 (time point) repeated measures analysis of variance (ANOVA) for each dependent variable. Caffeine resulted in a significantly lower session RPE (p < 0.05) for caffeine (6.1 ± 2.2) versus placebo (6.8 ± 2.1). Acute perceptual responses were significantly lower for caffeine for RPE overall (15, 20, 25, and 30 min), RPE breathing (15, 20, 25, and 30 min) and RPE legs (20 and 30 min). Survey responses post-exercise revealed greater feelings of nervousness, tremors, restlessness and stomach distress following caffeine versus placebo. Blunted acute RPE and survey responses suggest participants responded to caffeine ingestion. Caffeine decreased acute RPE during exercise which could partially account for lower session RPE responses. However, decreased session RPE could also reveal a latent analgesic affect of caffeine extending into recovery. Extending the understanding of session RPE could benefit coaches in avoiding overtraining when adjusting training programs.